PENGARUH MASASE PUNGGUNG TERHADAP PENURUNAN INTESITAS NYERI PERSALINAN KALA I FASE AKTIF PADA IBU PRIMIPARA DI WILAYAH KERJA PUSKESMAS BATU AJI KOTA BATAM TAHUN 2018 - Diana, Ella; Utami, Risqi (Universitas Batam, 2019)
Massage is a gentle pressure that helps a mother feel more refreshed, relaxed, and comfortable at childbirth. Massage, during phase of childbirth, also makes a mother feel closer to the person who cares for her. Many parts of the body of a pregnant woman can be massaged, one of which is the back. This study adopted a quantitative method, true experimental design, with the design used is posttest only control group design. The population was all primiparous pregnant women at Puskesmas Batu Aji area with a total sample of 60 respondents, using total sampling technique and this study was conducted on March to July 2018. Data collection applied observation, and back massage treatment. Research data was analyzed using the T-Test. In conclusion, there were significant differences in mean scores on the reducing maternal pain intensity in those who were not given treatment with those who were given treatment reduced by 1.03.It is suggested that respondents can apply according to the treatment given in the situation needed.